HALP Score and Disease Activity in Psoriatic Arthritis: Comparison with Healthy Controls - Zontul, Sezgin; Yolbaş, Servet; İnanç, Elif; Şimşek, Emrah; Arslan, Ahmet Kadir (The European Research Journal, 2026)
Objectives: This study evaluated the relationship between the haemoglobin-albumin-lymphocyte-platelet (HALP) score and disease activity in patients with psoriatic arthritis (PsA), and compared HALP scores between PsA patients and healthy controls. Methods: This single-centre, cross-sectional study included 73 PsA patients and 59 healthy controls. Demographic, clinical and laboratory data were collected. Disease activity was assessed using the Ankylosing Spondylitis Disease Activity Score (ASDAS) based on C-reactive protein (CRP), the Disease Activity index for Psoriatic Arthritis (DAPSA), the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the visual analogue scale (VAS), and the Psoriasis Area and Severity Index (PASI). HALP was calculated as haemoglobin × albumin × lymphocyte / platelet. Group comparisons, correlation analyses and ROC analyses were performed. Results: Compared with controls, PsA patients had higher CRP, erythrocyte sedimentation rate and platelet values, and lower albumin (all P